Communal responsibility and the coexistence of money and credit under anonymous matching - Lars Boerner; Albrecht Ritschl (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
Communal responsibility, a medieval institution studied by Greif (2006), supported the use of credit among European merchants in the absence of modern enforcement technologies. This paper shows how this mechanism helps to overcome enforcement problems in anonymous buyer/seller transactions. In a village economy version of the Lagos and Wright (2005) model, agents trading anonymously in decentralized markets can be identified by their citizenship and thus be held liable for each other. Enforceability within each village's centralized afternoon market ensures collateralization of credit in decentralized markets. In the resulting equilibrium, money and credit coexist in decentralized markets if the use of credit is costly. Our analysis easily extends itself to other payment systems like credit cards that provide a group identity to otherwise anonymous agents.
Keywords: E41; D51; N2; 330; communal responsibility; anonymous matching; money demand; credit; bills of exchange; Handelsforschung; Kredit; Rechtsdurchsetzung; Kreditsicherung; Matching; Zahlungsverkehr; Theorie